Where do students in the health professions want to work? - Birden Hudson; Fuller Jeffery; Fletcher Susan; Schofield Deborah; Page Sue (BMC, 2009)
Abstract Background Rural and remote areas of Australia are facing serious health workforce shortages. While a number of schemes have been developed to improve recruitment to and retention of the rural health workforce, they will be effective only if appropriately targeted. This study examines the factors that most encourage students attending rural clinical placements to work in rural Australia, and the regions they prefer. Methods The Careers in Rural Health Tracking Survey was used to examine the factors that most influence medical, nursing and allied health students' preference for practice locations and the locations preferred. Results Students showed a preference for working in large urban centres within one year, but would consider moving to a more rural location later in life. Only 10% of students surveyed said they would never work in a rural community with a population of less than 10 000. Almost half the sample (45%) reported wanting to work overseas within five years. The type of work available in rural areas was found to be the factor most likely to encourage students to practice rurally, followed by career opportunities and challenge Conclusion The decision to practise rurally is the result of a complex interaction between a number of factors including ethnicity, discipline, age and sex, among others. Incentives that aim to entice all students to rural practice while considering only one of these variables are likely to be inadequate.